The role of rodents circulating pathogenic leptospira in urban cities in peninsular Malaysia - Benacer, Douadi; Mohd Zain, Siti Nursheena; Sim, Shin Zhu; M. Nizam, Khairul; Thong, Kwai Lin (2015)
Leptospirosis is an infectious disease affecting both humans and animals and considered one of the common zoonotic disease worldwide. It is caused by spirochetes from the genus of Leptospira. Rodents have unambiguously served as reservoir for leptospires by shedding them through urine for extended periods. However, in Malaysia is a paucity of information of this disease in the rat population, which is considered the principal maintenance host of Leptospira and may be one of the possible transmission sources of leptospirosis in this country.